Co-Mn Complex Oxide Nanoparticles as Potential Reactive Oxygen Species Scavenging Agents for Pulmonary Fibrosis Treatment - Wuhao Yang; Hui Yuan; Hao Sun; Ting Hu; Yaping Xu; Yan Qiu; Yuhang Li (Molecules)
Idiopathic pulmonary fibrosis (IPF) is a chronic and age-related lung disease that has few treatment options. Reactive oxygen species (ROS) play an important role in the introduction and development of IPF. In the present study, we developed multifunctional Cobalt (Co)–Manganese (Mn) complex oxide nanoparticles (Co-MnNPs), which can scavenge multiple types of ROS. Benefiting from ROS scavenging activities and good biosafety, Co-MnNPs can suppress canonical and non-canonical TGF-β pathways and, thus, inhibit the activation of fibroblasts and the productions of extracellular matrix. Furthermore, the scavenging of ROS by Co-MnNPs reduce the LPS-induced expressions of pro-inflammatory factors in macrophages, by suppressing NF-κB signaling pathway. Therefore, Co-MnNPs can reduce the excessive extracellular matrix deposition and inflammatory responses in lungs and, thus, alleviate pulmonary fibrosis induced by bleomycin (BLM) in mice. Taken together, this work offers an anti-fibrotic agent for treatment of IPF and other ROS-related diseases.